A validation of the disability attitudes in health care scale using the Rasch analysis on a sample of Korean medical students. Issue 12 (5th June 2021) - Yi, You Gyoung; Lee, Jeong-Eun; Kim, Ye Il; Kim, Eunhae; Shin, Hyung-Ik
Abstract: Background and Purpose: The "Disability Attitudes in Health Care" scale contains 17 items and measures attitudes toward persons with disabilities in healthcare settings. This study aimed to analyze the psychometric properties of the Disability Attitudes in Health Care in order to improve its measurement quality. Materials and Methods: The Disability Attitudes in Health Care scale was administered to 272 students at a medical school. Rasch analysis was conducted to assess the category use, the overall fit of the model, and the person-item fit. Results: Compared to the previous 5-point Likert scoring system, the combination of category 1 (strongly disagree) and 2 (disagree), which transformed the Disability Attitudes in Health Care into a 4-point scale, was more appropriate. Items 2 and 13 had a poor fit with the model because of low construct homogeneity and low point-measure correlation, respectively; therefore, they were removed. However, there were not enough questions regarding the difficulty level for distinguishing medical students' attitudes toward persons with disabilities more sensitively. Conclusions: The results of this study suggest that constructing Disability Attitudes in Health Care with 15 items and using a 4-category scoring method could help to increase the scale's reliability and validity. The revised version of Disability Attitudes in Health Care could be of value to those who educate medical students and train rehabilitation professionals. IMPLICATIONS FOR REHABILITATION: Constructing a Disability Attitudes in Health Care scale with 15 items by using a 4-category scoring method could increase the reliability and validity of the scale. To improve the sensitivity of the Disability Attitudes in Health Care, it is necessary to add more difficult items to the scale. The Disability Attitudes in Health Care could be of value to those who educate medical students and train rehabilitation professionals.